Psikoedukasi Customer Relationship sebagai Optimalisasi Strategi Pemasaran di Warung X - Indraswari, Candra; Prasasti, Indira; Wardhani, Hanis Kusuma; Warrowa, Vinka (Universitas Islam Negeri Raden Intan Lampung, 2021)
AbstractBusiness actors such as food stalls or places to eat are one of the various actors in the business world affected during the pandemic. The growth in the business area has also caused in the emergence of an increasingly strong competition between business actors. Service to consumers is one of strategy to attract customers. The purpose of this study was to determine the customer relationship strategy at Warung X. The type of the method used in this study was a qualitative with case study approach. There were four informants and data collected by observation and interview. Data was then analyzed by reducing, displaying, and drawing conclusions. The results showed that the customer relationship strategy has not been effective, so the researchers conducted psychoeducation to optimize the strategy. This was done in order to create a good image to customers.Keywords: Case study, customer relationship, psychoeducation, Warung X